Developing and Testing the Populi Needle Exchange Point Finder: An App to Reduce Harm Associated With Intravenous Drug Consumption Among Homeless and Non-homeless Drug Users - Calvo, Fran; Carbonell, Xavier; Mundet, Carles (Frontiers in Public Health, 2020)
The spread of viral infections remains a serious public health problem. People who inject drugs represent one of the highest-risk groups. eHealth and mHealth have been shown to be effective in improving individuals' management of their own health and their access to health care and to contribute to reducing the costs associated with certain medical interventions. People who inject drugs, including homeless people, tend to have access to technology. Young homeless people in particular are likely to use smartphones and social networking sites in ways that are similar to the general population. Despite this widespread use of technology, there are no apps designed specifically to reduce harm in people who inject drugs. The objective of this study is to analyze the development and usability testing process for an application for mobile devices, designed to complement the Needle Exchange Program. This app—the first of its kind—was developed by a public health agency, specialized professionals and people who inject drugs. We analyzed the differences in how health providers and drug users experienced the usability of the app. The participants were 61 members of multidisciplinary professional group and 16 people who inject drugs. We used a cross-sectional quantitative, observational design. First, we created and administered a questionnaire to collect the sociodemographic characteristics that could mediate the use of technology. Next participants tried the app and filled out a second questionnaire in which they rated their experience on a Likert scale from 1 to 7 in the following dimensions: overall attractiveness of the app, ease/difficulty of use, the extent to which they believed the app could improve access to injection materials, the extent to which they thought it would improve PWID's participation in the needle exchange program, overall utility, the degree to which they thought PWID would use the app, and the need for the app. To analyze the answers, we used contingency tables and compared means using a Student's t test. Finally, we conducted six audio-recorded focus groups about how the participants experienced the usability of the app. The objective of this part of the study was to classify and quantify the contributions of individuals and the group according to three predefined categories: potential benefits and positive aspects, potential obstacles or difficulties in carrying out the project, and concrete suggestions for improving the interface. There were not significant differences between the sociodemographic variables and the variables related to use of the app between professionals and PWID. Both professionals and PWID rated the app as intuitive and useful, especially the geolocation function for NEPs. Both groups also thought that the interface contained too much information and that this excess could be confusing for users. Both groups also had similar opinions about the app and its uses. An important difference between the two groups is that PWID reported that they would use the app, while professionals reported that they didn't think PWID would use it. All participants proposed improvements on the prototype, suggestions that will be applied in the creation of the definitive interface. Including professionals and patients in this sort of usability test enables researchers and developers to detect the needs of potential app users.